Leber’s hereditary optic neuropathy companied with multiple-related diseases - Sun, Ming-ming; Zhou, Huan-fen; Sun, Qiao; Li, Hong-en; Liu, Hong-juan; Song, Hong-lu; Yang, Mo; Teng, Da; Wei, Shi-hui; Xu, Quan-gang (Frontiers in Human Neuroscience, 2022)
Objective To elucidate the clinical, radiologic characteristics of Leber’s hereditary optic neuropathy (LHON) associated with the other diseases. Materials and methods Clinical data were retrospectively collected from hospitalized patients with LHON associated with the other diseases at the Neuro-Ophthalmology Department at the Chinese People’s Liberation Army General Hospital (PLAGH) from December 2014 to October 2018. Results A total of 13 patients, 24 eyes (10 men and 3 women; mean age, 30.69 ± 12.76 years) with LHON mitochondrial DNA (mtDNA) mutations, were included in the cohort. 14502(5)11778(4)11778 &11696(1)12811(1)11696(1)3460(1). One patient was positive for aquaporin-4 antibody (AQP4-Ab), and two were positive for myelin oligodendrocyte glycoprotein antibody (MOG-Ab). Three patients were associated with idiopathic optic neuritis (ON). Two patients were with compression optic neuropathy. Three patients were with the central nervous system (CNS) diseases. One patient was with proliferative diabetic retinopathy (PDR) and one with idiopathic orbital inflammatory syndrome (IOIS). At the onset, visual acuity (VA) in eighteen eyes was below 0.1, one eye was 0.5, five eyes were above 0.5, while VA in sixteen eyes was below a 0.1 outcome, three eyes experienced moderate vision loss. MRI images showed T2 lesions and enhancement in nine patients who received corticosteroids treatment; additional immune modulators treatment was performed on two patients. None of the patients had relapse during the follow-up time. Conclusion Leber’s hereditary optic neuropathy can be accompanied with multiple-related diseases, especially different subtypes of ON, which were also exhibited with IOIS and compression optic neuropathy for the first time in this cohort. This condition may be a distinct entity with an unusual clinical and therapeutic profile.